Xenophobia, nationalism and COVID-19: the construction of the Venezuelan migrant in the discourse on vaccination in social networks - Vega, Josseline (2022)
Venezuelan migration is considered the most important migratory phenomenon in Latin America in the last two decades and the subjects who migrate face social violations in access to services and xenophobic marginalization in the countries that receive them. This paper aims to identify the identity instances from which the Venezuelan migrant is constructed in social networks within the discourse on vaccination against COVID-19. Comments are collected on Twitter and Facebook during the month of May 2021. The analysis explains the identity instances from two angles: nationalism and the Venezuelan migrant constructed as a threat. It is concluded that the networks function as a impeller of spaces in which xenophobia is patent. Both nationalist statements and those of the migrant-threat are not only xenophobic per se, but serve as an argument to justify the migrant's non-entitlement to vaccination and access to health in general.